HUBUNGAN PERILAKU MENYIKAT GIGI DAN KARIES GIGI MOLAR PERTAMA PERMANEN PADA SISWA KELAS V DI SDN 4 PENDEM TAHUN 2018 - Anak Agung Gede Agung; Ni Kadek Enyk Parmita Dewi (Jurnal Kesehatan Gigi (Dental Health Journal), 2019)
HL Blum states that, the degree of health of a person or community is influenced by four factors, namely: environment, behavior, heredity, and health services. According to Laurence Green there are three factors that influence one's behavior, namely predisposing factors, supporting factors, and reinforcing factors. The biggest problem faced by the Indonesian population as well as in other developing countries in the field of dental and oral health is the disease of hard tooth tissue (caries dentis) besides gum disease. Ni Kadek Enyk Parmita Dewi's research concluded that, most students behave to brush their teeth with the criteria need guidance. The frequency of fifth grade students suffering from caries in permanent first molars was 24 people (54.55%). The average caries of permanent first molars was 0.82. The purpose of this study was to determine the behavior of tooth brushing with dental caries in class V students at SDN 4 Pendem Jembrana in 2018. This type of cross sectional study, uses secondary data from Ni Kadek Enyk Parmita Dewi's research. Spearmen correlation test results between dental caries variables with tooth brushing behavior obtained sig values. 0.015. Conclusion there is a relationship between the variables of tooth brushing behavior with dental caries in fifth grade students at SDN 4 Pendem Jembrana in 2018.